2017
DOI: 10.1002/eat.22787
|View full text |Cite
|
Sign up to set email alerts
|

Testing predictions of the emotion regulation model of binge‐eating disorder

Abstract: The association between difficulties in ER and ED pathology in BED suggests that treatments focusing on improving ER skills may be effective in treating this ED; however, the moderating effect of depression underscores the need for research on individual differences and treatment moderators. These findings suggest the importance of ER in understanding and treating BED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 67 publications
3
25
0
1
Order By: Relevance
“…All procedures were approved by the regional health research ethics board. Recruitment procedures are reported elsewhere (Kenny, Singleton, & Carter, 2017;Kenny, Van Wijk, Singleton, & Carter, 2018). Briefly, individuals with BED and NED were recruited from the community via social media, radio interviews, and posters.…”
Section: Methodsmentioning
confidence: 99%
“…All procedures were approved by the regional health research ethics board. Recruitment procedures are reported elsewhere (Kenny, Singleton, & Carter, 2017;Kenny, Van Wijk, Singleton, & Carter, 2018). Briefly, individuals with BED and NED were recruited from the community via social media, radio interviews, and posters.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, binge eating and binge drinking often co-occur suggesting that there are some overlapping features between these behaviors (Ferriter & Ray, 2011;Laghi et al, 2014). Hence, understanding mechanisms underlying adolescents' binge behaviors could be helpful to design supportive intervention programs in favor of youth (Kenny, Singleton, & Carter, 2017).…”
Section: Satisfactionmentioning
confidence: 99%
“…It has even been suggested that de cits in emotion regulation are predisposing factors for the development of ED [9,8,6]. Patients with ED have reported poorer emotional awareness, emotional suppression, less use of adaptive emotional regulation strategies, and greater use of maladaptive emotional regulation strategies compared to people in healthy control groups [10,11,12,13,14,15,6].…”
Section: Introductionmentioning
confidence: 99%